'Sobriety, human dignity and public morality': ethical standards in Kazakhstan. Issue 2 (17th February 2023) - Pelizzo, Riccardo; Knox, Colin
ABSTRACT: Kazakhstan, like other post-Soviet countries, is struggling to address residual issues of corruption and weak ethical standards within a wider initiative to promote good governance. From 1997 onwards, it has introduced several iterations of codes of ethics and professional conduct. These efforts have culminated in the appointment of ethics commissioners in each ministry and government agency. This article considers how effective they have been in enforcing ethical standards through primary data collected from three groups: aspiring civil servants; in-service officials; and, ethics commissioners. The research finds that commissioners have much higher tolerance levels towards ethical dilemmas and lack consistency in making judgements, which limits confidence in their roles as enforcement officers.